Association Between Lack of Insight and Prefrontal Serotonin Transporter Availability in Antipsychotic-Free Patients with Schizophrenia: A High-Resolution PET Study with [11C]DASB - Kim JH (Dove Medical Press, 2021)
Jeong-Hee Kim,1,2 Young-Don Son,1– 3 Hang-Keun Kim,1– 3 Jong-Hoon Kim1,3,4 1Neuroscience Research Institute, Gachon University, Incheon, Republic of Korea; 2Department of Biomedical Engineering, College of Health Science, Gachon University, Incheon, Republic of Korea; 3Gachon Advanced Institute for Health Sciences & Technology, Gachon University, Incheon, Republic of Korea; 4Department of Psychiatry, Gachon University College of Medicine, Gil Medical Center, Incheon, Republic of KoreaCorrespondence: Jong-Hoon KimDepartment of Psychiatry, Gachon University College of Medicine, Gil Medical Center, 1198 Guwol-dong, Namdong-gu, Incheon, 21565, Republic of KoreaTel +82 32 460 2696Fax +82 32 472 8813Email jhnp@chol.com; jhnp@gachon.ac.krYoung-Don SonDepartment of Biomedical Engineering, College of Health Science, Gachon University, 191 Hambakmoe-ro, Yeonsu-gu, Incheon, 21936, Republic of KoreaTel +82 32 820 4416Email ydson@gachon.ac.krBackground: Previous studies suggested a link between serotonergic neurotransmission and impaired insight in schizophrenia. In this study, we examined the relationship between serotonin transporter (SERT) availability in regions of the prefrontal cortex (dorsolateral, ventrolateral, ventromedial, and orbitofrontal cortices) and insight deficits in antipsychotic-free patients with schizophrenia using high-resolution positron emission tomography (PET) with [11C]DASB.Methods: Nineteen patients underwent [11C]DASB PET and 7-Tesla magnetic resonance imaging scans. To assess SERT availability, the binding potential with respect to non-displaceable compartment (BPND) was derived using the simplified reference tissue model. Patients’ level of insight was assessed using the Insight and Treatment Attitude Questionnaire (ITAQ). The relationship between ITAQ scores and [11C]DASB BPND values was examined using the region-of-interest (ROI)- and voxel-based analyses with relevant variables as covariates. The prefrontal cortex and its four subregions were selected as a priori ROIs since the prefrontal cortex has been implicated as the critical neuroanatomical substrate of impaired insight in schizophrenia.Results: The ROI-based analysis revealed that the ITAQ illness insight dimension had significant negative correlations with the [11C]DASB BPND in the left dorsolateral, left orbitofrontal, and bilateral ventrolateral prefrontal cortices. The ITAQ treatment insight dimension had significant negative correlations with the [11C]DASB BPND in the bilateral dorsolateral, left orbitofrontal, and bilateral ventrolateral prefrontal cortices. The ITAQ total score showed significant negative correlations with the [11C]DASB BPND in the bilateral prefrontal cortex and three subregions (dorsolateral, ventrolateral, and orbitofrontal cortices). A supplementary voxel-based analysis corroborated a significant negative association between the ITAQ score and the [11C]DASB BPND in the prefrontal cortices.Conclusion: Our study provides in vivo evidence of significant negative correlations between insight deficits and prefrontal SERT availability in patients with schizophrenia, suggesting significant involvement of prefrontal serotonergic signaling in impaired insight, one of the core symptoms of schizophrenia.Keywords: insight, schizophrenia, serotonin transporter, prefrontal cortex, [11C]DASB, positron emission tomography